2008
DOI: 10.1364/ol.33.000560
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-purity-enhancing layer for multilayer mirrors

Abstract: We demonstrate, both theoretically and experimentally, that special spectral-purity-enhancing multilayer mirror systems can be designed and fabricated to substantially reduce the level of out-of-band radiation expected in an extreme ultraviolet lithographic tool. A first proof of principle of applying such spectral-purity-enhancement layers showed reduced out-of-band reflectance by a factor of five, while the in-band reflectance is only 4.5% (absolute) less than for a standard capped multilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…Returning to the first proof of principle by van Herpen [2], which showed that an AARC of 7 nm of Si 3 N 4 suppressed the reflectance of 160 nm radiation of a Mo/Si MLM by a factor of 5 at a loss of 4.5% absolute EUV reflectance, our results demonstrate that theoretically there is much room for improvement. With the appropriate optical constants, the DUV reflectance could be further reduced to below 10 −3 using an even thinner AARC, which will further reduce the losses in EUV reflectance, assuming the optical constants of the AARC in the EUV remain identical.…”
Section: Simulation Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Returning to the first proof of principle by van Herpen [2], which showed that an AARC of 7 nm of Si 3 N 4 suppressed the reflectance of 160 nm radiation of a Mo/Si MLM by a factor of 5 at a loss of 4.5% absolute EUV reflectance, our results demonstrate that theoretically there is much room for improvement. With the appropriate optical constants, the DUV reflectance could be further reduced to below 10 −3 using an even thinner AARC, which will further reduce the losses in EUV reflectance, assuming the optical constants of the AARC in the EUV remain identical.…”
Section: Simulation Resultssupporting
confidence: 58%
“…The interference effects in such a Fabry-Perot type resonator rely on the high transparancy of the non-absorbing dielectric medium, as the optical phaseshift is acquired over multiple passes within the cavity. Recently, multiple studies [1][2][3][4][5] have shown that antireflection resonance can also be achieved in highly absorbing thin films with a thickness far below the quarter-wave limit. These absorbing antireflection coatings (AARC) are ideally suitable for applications that, in addition to strong requirements of the reflectance, impose strict limitations on the thickness of the AARC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…87 For EUV lithography systems, a UV ARC is considered as part of the high reflectance multilayer coated optics. 88 The challenge in designing and engineering UV ARCs specifically for that purpose lies in the fact that the EUV transmission (e.g., around 13.5 nm) cannot be compromised. This limits the available range of materials for the antireflection coatings to those with very low absorption in the EUV range.…”
Section: Uv Anti-reflectionmentioning
confidence: 99%
“…For the 100-200 nm wavelength range, the optical properties of Si 3 N 4 are favorable for a single layer ARC design and the development of a 7 nm-thick Si 3 N 4 on top of a high reflectance Mo/Si multilayer has been described in Ref. 88. The relatively weak absorption of Si 3 N 4 at 13.5 nm limits the loss of EUV reflectivity to only 4%, while reducing the UV reflectivity by a factor of 5.…”
Section: Uv Anti-reflectionmentioning
confidence: 99%